2019
DOI: 10.1186/s13073-019-0672-4
|View full text |Cite
|
Sign up to set email alerts
|

Relating the gut metagenome and metatranscriptome to immunotherapy responses in melanoma patients

Abstract: Background Recent evidence suggests that immunotherapy efficacy in melanoma is modulated by gut microbiota. Few studies have examined this phenomenon in humans, and none have incorporated metatranscriptomics, important for determining expression of metagenomic functions in the microbial community. Methods In melanoma patients undergoing immunotherapy, gut microbiome was characterized in pre-treatment stool using 16S rRNA gene and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
223
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(234 citation statements)
references
References 45 publications
7
223
3
1
Order By: Relevance
“…Across cohorts, patients with non-GI cancers have altered gut microbial communities Given our success integrating results of the MI cohort with those from Zeevi et al 2015, we sought to determine whether similar congruence was observed in the gut microbiome of cancer patients. We focused on those with non-GI tumors, for whom recent publications have demonstrated associations between microbiome composition and positive responses to checkpoint inhibitors (Frankel et al, 2017;Gopalakrishnan et al, 2018;Matson et al, 2018;Peters et al, 2019;Routy et al, 2018). In contrast to colorectal cancer (Thomas et al, 2019), there remains a large gap in our knowledge detailing how the microbiome composition of cancer patients with non-GI indications compares to that of healthy donors.…”
Section: Short-term Stability Is Variable Across Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across cohorts, patients with non-GI cancers have altered gut microbial communities Given our success integrating results of the MI cohort with those from Zeevi et al 2015, we sought to determine whether similar congruence was observed in the gut microbiome of cancer patients. We focused on those with non-GI tumors, for whom recent publications have demonstrated associations between microbiome composition and positive responses to checkpoint inhibitors (Frankel et al, 2017;Gopalakrishnan et al, 2018;Matson et al, 2018;Peters et al, 2019;Routy et al, 2018). In contrast to colorectal cancer (Thomas et al, 2019), there remains a large gap in our knowledge detailing how the microbiome composition of cancer patients with non-GI indications compares to that of healthy donors.…”
Section: Short-term Stability Is Variable Across Donorsmentioning
confidence: 99%
“…In contrast to colorectal cancer (Thomas et al, 2019), there remains a large gap in our knowledge detailing how the microbiome composition of cancer patients with non-GI indications compares to that of healthy donors. To investigate this, we applied our Kraken2/GTDB pipeline to an additional 375 samples from 283 cancer patients across five published cohorts (Frankel et al, 2017;Gopalakrishnan et al, 2018;Matson et al, 2018;Peters et al, 2019;Routy et al, 2018; Fig. S4, A-E).…”
Section: Short-term Stability Is Variable Across Donorsmentioning
confidence: 99%
“…Peter et al [ 135 ], in studies on 27 metastatic melanoma patients, also demonstrated the correlation between gut microbiota composition and ICI therapy effects (anti-PD-1 therapy, n = 14; anti-CTLA-4 therapy, n = 1; anti-PD-1/anti-CTLA-4 therapy, n = 12). Coprococcus eutactus , Prevotella stercorea , Streptococcus sanguinis , Streptococcus anginosus , and Lachnospiraceae bacterium 3 1 46FAA and previously found Faecalibacterium prausnitzii were identified in patients with longer PFS, whereas Bacteroides ovatus , Bacteroides dorei , Bacteroides massiliensis , Ruminococcus gnavus , and Blautia producta were present in the gut microbiota of patients with poor clinical outcomes.…”
Section: Predictive Biomarkers Related To the Host Gut Microbiotamentioning
confidence: 99%
“…The vast majority are prospective studies. Among them, 10 studies [6,9,[12][13][14][15][16][17][18][19] had response/e cacy data and 3 studies [17,20,21] had AEs data using ICI therapy, and 1 study had both [17]. Of note, the documented AEs in that 3 studies [17,20,21] were virtually all irAEs.…”
Section: Common Features In Gut Microbiome Correlate With the Treatmementioning
confidence: 99%